Altering native community assembly history influences the performance of an annual invader - Hess, Manon C.M.; Mesléard, François; Young, Truman P.; de Freitas, Benoit; Haveneers, Nathan; Buisson, Elise (Basic and applied ecology, 2022)
Understanding the determinants of early invasion resistance is a major challenge for designing plant communities that efficiently repel invaders. Recent evidence highlighted the significant role of priority effects in early community assembly as they affect species composition, structure and functional properties, but the consequences of native community assembly history on the success of subsequent invasions has not been elucidated yet. In a greenhouse experiment, we investigated how (1) the identity of the first native colonizing species (one of two grasses: Dactylis glomerata and Lolium perenne, or two legumes: Onobrychis viciifolia and Trifolium repens), each introduced four weeks before the rest of the native community, and (2) timing of species establishment (synchronous vs. sequential sowing), influenced early establishment success of Ambrosia artemisiifolia, an annual noxious weed in Europe. First colonizer identity and establishment timing both affected early biomass production and composition of the community, and had implications for A. artemisiifolia early invasion success. Invasion success decreased when all native individuals were sown simultaneously, quickly generating a high biomass production, while it increased when the productive N-fixing legume T. repens was sown first. These findings support that native species assembly history matters to invasion resistance in the early growth stages, thus opening the way to more effective invasive species management strategies in restoration.